Benditos Amaros - remanescentes quilombolas de Paracatu: memórias, lutas e práticas culturais (1940-2004) - Silva, Paulo Sérgio Moreira da (2012)
The research of Family Amaros is, in some sense, the continuity of the master thesis, entitled The Caretagem as cultural practice: faith, blackness and revelry in Paracatu, MG(1960-1980) and, consequently, the induced understand its displacement relative to a neighborhood on the outskirts of the city of Paracatu and understand their wiles and cultural resistance, especially with regard to the struggles and conflicts that have undertaken the process of resuming possession of their lands and farm Pituba. In this sense, this research on the family of Amaros aimed to deepen their ritual context, which aims to establish a dialogue that goes beyond a simple reading of the daily life they represent, because the trajectory envisioned an understanding of family and kinship network woven from cultural shaped face and survive the social and political issues experienced. In vieis, this agenda is the political struggle for social rights of the family land located on the farm of Amaros, Pituba, from which they were expropriated from the year 1940. In this political process was evidence the persistence of the values and traditions of African descent enrolled in a memory that moved to the urban periphery recreate their culture, their way of life, combining the family around their celebrations, sociability, arts and craft activities as a way of living maintain their cultural identity. From this point of view, we conceive the political struggle for recognition of their land and social rights embedded in their daily lives for their popular cultural practices, hence, the focus not only on their movement around the Palmares Cultural Foundation and the Institute for Black Speech, but also the set of symbolic representations that protect their cultural identity through a social memory in continuous recreation / reinvention.